2020
DOI: 10.1186/s40623-020-01169-3
|View full text |Cite
|
Sign up to set email alerts
|

Submarine landslide source models consistent with multiple tsunami records of the 2018 Palu tsunami, Sulawesi, Indonesia

Abstract: Previous studies have suggested submarine landslides as sources of the tsunami that damaged coastal areas of Palu Bay after the 2018 Sulawesi earthquake. Indeed, tsunami run-up heights as high as 10 m determined by field surveys cannot be explained by the earthquake source alone although the earthquake is definitely the primary cause of the tsunami. The quantitatively reexamined results using the earthquake fault models reported so far showed that none of them could fully explain the observed tsunami data: tsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
51
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 36 publications
5
51
0
1
Order By: Relevance
“…Although there are now many tsunami simulations of the 2018 Palu event (e.g., Heidarzadeh et al, 2019;Takagi et al, 2019;Carvajal et al, 2019;Pakoksung et al, 2019;Gusman et al, 2019;Jamelot et al, 2019;Ulrich et al, 2019;Goda et al, 2019;Nakata et al, 2020;Sepúlveda et al, 2020;Liu et al, 2020, see summary of studies characteristics in Table 1), the tsunami mechanism, earthquake, coastal landslides, or both in combination, is still uncertain. In addition, whereas many published models simulate some, or even most, recorded runups around the Bay, the mechanisms are often ad hoc and do not reproduce the timing of tsunami waves from eyewitness accounts or the video evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are now many tsunami simulations of the 2018 Palu event (e.g., Heidarzadeh et al, 2019;Takagi et al, 2019;Carvajal et al, 2019;Pakoksung et al, 2019;Gusman et al, 2019;Jamelot et al, 2019;Ulrich et al, 2019;Goda et al, 2019;Nakata et al, 2020;Sepúlveda et al, 2020;Liu et al, 2020, see summary of studies characteristics in Table 1), the tsunami mechanism, earthquake, coastal landslides, or both in combination, is still uncertain. In addition, whereas many published models simulate some, or even most, recorded runups around the Bay, the mechanisms are often ad hoc and do not reproduce the timing of tsunami waves from eyewitness accounts or the video evidence.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the Palu tsunami, the submarine landslide source was implemented by using a combination of models, namely, Titan2D (Pitman et al 2003;Patra et al 2005; Titan2D 2016) and JAGURS (Baba et al 2017), with a multi-landslide location in the bay. The volume of the multi-landslide source varied from 0.02 to 0.07 km 3 among six different locations (Nakata et al 2020). In addition, the TUNAMI-N2 model was applied to model the submarine landslide-induced tsunami in Palu Bay by Pakoksung et al (2019), who proposed that the main source of the landslide that generated the 2018 Palu tsunami was in the northern part of the bay.…”
Section: Introductionmentioning
confidence: 99%
“…The tsunamis are mostly generated by large earthquakes with minor occurrence of volcanic eruptions. Apart from the 2018 submarine landslide-generated tsunami in Sulawesi (Nakata et al, 2020), there is no other record of tsunami generated by submarine landslide in this region. A statistical study of historical tsunamis in the Philippines by Nakamura (1978) showed that the southern Mindanao area which includes the Sulu and Cotabato Trenches has the highest probability of tsunami occurrence, once in 10 years with waves reaching 7.8 m in height.…”
Section: Historical Tsunamis Around Sabahmentioning
confidence: 99%